2021
DOI: 10.1155/2021/3431245
|View full text |Cite
|
Sign up to set email alerts
|

TRAF6 Promoted Tumor Glycolysis in Non‐Small‐Cell Lung Cancer by Activating the Akt‐HIFα Pathway

Abstract: TRAF6 has been reported to be associated with poor prognosis in non-small-cell lung cancer (NSCLC). However, its precise role in tumor development has not been elaborated. In the present study, the function and the mechanism by which TRAF6 contributes to development were intensively investigated. TRAF6 was found to be overexpressed in primary NSCLC tumor tissue and all tested cell lines. Knockdown of TRAF6 with shRNA substantially attenuated NSCLC cell proliferation and anchorage-independent growth. Moreover, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…The up-regulation of glycolysis levels has been observed in many cancers, including primary and metastatic cancers, and aerobic glycolysis is the most commonly used and preferred mechanism of glucose metabolism in cancer cells [ 54 ]. Previous studies [ 55 , 56 , 57 , 58 , 59 , 60 , 61 ] showed that signaling pathways such as Akt, Myc, ERK, and NF-κB play an important regulatory role during glycolysis. In NSCLC, high levels of glucose transporter 1 (GLUT1) and hexokinase 2 (HK2) promoted glucose uptake by lung cancer cells, which was the initial step of glucose metabolism [ 62 , 63 ].…”
Section: Resultsmentioning
confidence: 99%
“…The up-regulation of glycolysis levels has been observed in many cancers, including primary and metastatic cancers, and aerobic glycolysis is the most commonly used and preferred mechanism of glucose metabolism in cancer cells [ 54 ]. Previous studies [ 55 , 56 , 57 , 58 , 59 , 60 , 61 ] showed that signaling pathways such as Akt, Myc, ERK, and NF-κB play an important regulatory role during glycolysis. In NSCLC, high levels of glucose transporter 1 (GLUT1) and hexokinase 2 (HK2) promoted glucose uptake by lung cancer cells, which was the initial step of glucose metabolism [ 62 , 63 ].…”
Section: Resultsmentioning
confidence: 99%
“…TRAF6 exhibits high expression levels in breast cancer, particularly in cases with bone and brain metastases, and its expression is inversely correlated with breast cancer prognosis. Strategies aimed at reducing TRAF6 expression have been shown to inhibit the proliferation and metastasis of breast cancer cells [ 33 ]. These findings collectively underscore the intimate link between TRAF family genes and tumor development.…”
Section: Discussionmentioning
confidence: 99%
“…Pathway enrichment analysis shows that these genes may be involved in various signaling pathways, such as PI3K-Akt signaling pathway, IL-17 signaling pathway, and endocrine resistance. AKT1 is an important signal pathway factor, which participates in all stages of lung cancer occurrence and development [ 29 ]; IL-17 can promote angiogenesis through the VEGF pathway, which may indirectly increase the production of NO in the lungs of NSCLC patients and promote the invasion and metastasis of lung cancer [ 30 ]. Therefore, these signaling pathways execute different functions in the occurrence and development of lung cancer, while Fisetin may play an intervention role by regulating these signaling pathways.…”
Section: Discussionmentioning
confidence: 99%